2012
DOI: 10.1007/s00360-012-0717-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited capacity for acclimation of thermal physiology in a salamander, Desmognathus brimleyorum

Abstract: Habitats vary in temperature both spatially and temporally. Variation in thermal habitat introduces challenges to organisms and may reduce fitness unless organisms can physiologically adjust to such changes. Theory predicts that thermal variability should influence the capacity for acclimation such that increased variation should favor a reduction in the thermal sensitivity of physiological traits. In this study, we investigated acclimation to constant and variable conditions in populations of the salamander D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…We calculated Q 10 values over 58C increments across the entire thermal range tested to examine for differences in thermal sensitivity of metabolic rate. The Q 10 values indicate the factor by which a physiological process (e.g., metabolic rate) changes as a result of a 108C increase in temperature, with a value of 1.0 indicating that change is temperature independent (Dorcas et al, 2004;Homyack et al, 2010;Young and Gifford, 2013). For each 58C increment we report mean Q 10 values (61 SE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated Q 10 values over 58C increments across the entire thermal range tested to examine for differences in thermal sensitivity of metabolic rate. The Q 10 values indicate the factor by which a physiological process (e.g., metabolic rate) changes as a result of a 108C increase in temperature, with a value of 1.0 indicating that change is temperature independent (Dorcas et al, 2004;Homyack et al, 2010;Young and Gifford, 2013). For each 58C increment we report mean Q 10 values (61 SE).…”
Section: Methodsmentioning
confidence: 99%
“…Each trial was separated by at least 48 h, between which subjects were returned to their housing conditions. Preliminary testing and previous research indicated that lungless salamander metabolic rates stabilize after 3 h Young and Gifford, 2013). We chose to record VO 2 consumption over a 6-h session using the first 3 h to allow for metabolic stabilization and the last 3 h for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…In the first, swimming performance was determined as a function of temperature in salamanders. Both T opt,stat and maximal performance were normally distributed among individuals, with a greater than two-fold range evident in maximal performance (Young and Gifford, 2013). In the second, critical heart rate temperature (H crit , the temperature at which cardiac function declines) was determined in mussels collected from a range of intertidal sites along the West coast of North America and then maintained under common garden conditions for at least a month before measurement (Logan et al, 2012).…”
Section: Spatial Variability Among Individuals In How They Experiencementioning
confidence: 99%
“…To assay CTMax, individuals were placed on a moist paper towel substrate in an opaque plastic container under a 100w ceramic infra-red heat emitting bulb (Zoo Med brand) (Layne & Claussen, 1982;Young & Gifford, 2013). Salamanders were constantly misted during the heating trials to avoid desiccation and were monitored for signs of behavioral abnormalities.…”
Section: Physiology and Ctmaxmentioning
confidence: 99%
“…LRR was achieved when an individual was unable to right itself after 30 seconds on its back on a moist surface (W. I. Lutterschmidt & Hutchison, 1997;Young & Gifford, 2013). At this time temperature was recorded with an IR temperature gun 1cm from the dorsal and ventral surface of the body.…”
Section: Physiology and Ctmaxmentioning
confidence: 99%